Genetic structure in the nonbreeding range of rufa Red Knots suggests distinct Arctic breeding populations ... - Verkuil, Yvonne; Tavares, Erika; González, Patricia M.; Choffe, Kristen; Haddrath, Oliver; Peck, Mark; Niles, Lawrence J.; Baker, Allan J.; Piersma, Theunis; Conklin, Jesse R. (Dryad, 2020)
An understanding of the migratory connectivity between breeding and nonbreeding areas is fundamental to the management of long-distance migrants under pressure from habitat change along their flyways. Here we describe evidence for genetic structure within the nonbreeding range of the endangered Arctic-Canadian rufa subspecies of Red Knots (Calidris canutus). Using blood and tissue samples from the major nonbreeding regions in Argentina (Tierra del Fuego and Río Negro), northern Brazil (Maranhão), and southeastern USA (Florida), we estimated genetic structure in 514 amplified fragment length polymorphism (AFLP) loci, applying cluster assignment analyses in DAPC, assignPOP, and STRUCTURE. Using a priori location information, individuals could be correctly re-assigned to their nonbreeding regions, which validated that the assignment accuracy of the data was sufficient. Without using a priori location information, we detected 3–5 genotype clusters, and posterior assignment probabilities of samples to these ... : Samples in Argentina, N Brazil and SE USA were collected over various years and sites which allows to control for batch effects. Samples were collected during the boreal winter, except for Río Negro, Argentina, which only hosts birds during the migratory season.To understand the relative scale of potential differences and to ensure our sample collection contained rufa only, the subspecies C. c. roselaari was included. For this subspecies, samples were included from a stopover area in NW USA (Alaska) and from a non-breeding area in Mexico. For this study we apply a few hundred AFLP markers aquired by standard lab procedures as described in the paper. The data was analysed with population genetics software packages, as described in the paper. ...